On Counting and Embedding a Subclass of Height-Balanced Trees - Indhumathi Raman (Modelling and Simulation in Engineering)
A height-balanced tree is a rooted binary tree in which, for every vertex v, the difference in the heights of the subtrees rooted at the left and right child of v (called the balance factor of v) is at most one. In this paper, we consider height-balanced trees in which the balance factor of every vertex beyond a level is 0. We prove that there are 22t-1 such trees and embed them into a generalized join of hypercubes.